The Cryptocurrency Market: A scale development study on the behaviors of investors - Taşhan, Ahmet (Technium Social Sciences Journal, 2025)
This research aims to develop a fear of missing out on the opportunities scale in the cryptocurrency market (CFOMO). This research is methodologically designed. The scale was applied to 116 cryptocurrency market investors. Exploratory and confirmatory factor analyses were used to test the construct validity of the scale, and internal consistency coefficient, item-total correlation, and test-retest analysis were used for reliability. The KMO value (0.882) and Barttlet’s test results (433.775) were statistically significant due to the Principal Component Analysis, which determined the suitability of the scale for construct validity testing. The reliability coefficient of the scale was calculated as 0.82. As a result of confirmatory factor analysis, X2=27.396, df=26 (p<0.05), X2/df=1.054, RMSEA=0.022, GFI=0.95, CFI=0.99 and IFI=0.99 revealed that the model showed good fit. The findings of the study showed that the CFOMO scale is valid and reliable.